Bulgecin A: a novel inhibitor of binuclear metallo-β-lactamases - SIMM, Alan M.; LOVERIDGE, E. Joel; CROSBY, John; AVISON, Matthew B.; WALSH, Timothy R.; BENNETT, Peter M. (Biochemical journal, 2005)
Bulgecin A, a sulphonated N-acetyl-D-glucosamine unit linked to a 4-hydroxy-5-hydroxymethylproline ring by a β-glycosidic linkage, is a novel type of inhibitor for binuclear metallo-β-lactamases. Using steady-state kinetic analysis with nitrocefin as the β-lactam substrate, bulgecin A competitively inhibited the metallo-β-lactamase BceII from Bacillus cereus in its two-zinc form, but failed to inhibit when the enzyme was in the single-zinc form. The competitive inhibition was restored by restoring the second zinc ion. The single-zinc metallo-β-lactamase from Aeromonas veronii bv. sobria, ImiS, was not inhibited by bulgecin A. The tetrameric L1 metallo-β-lactamase from Stenotrophomonas maltophilia was subject to partial non-competitive inhibition, which is consistent with a kinetic model in which the enzyme bound to inhibitor retains catalytic activity. Docking experiments support the conclusion that bulgecin A co-ordinates to the zinc II site in metallo-β-lactamases via the terminal sulphonate group on the sugar moiety.